Resiliência da agricultura familiar no nordeste brasileiro - Lira, Jaqueline Saraiva de (2016)
Family farming in the Brazilian Northeast is very susceptible to the impacts of climate change. However, the agricultural sector can get ability to adapt to the risks, whether climatic or not, through investments in planning strategies for development in rural areas. Thus, the aim of this study was to assess the resilience of family farming production in Northeastern of Brazil from 1990 to 2012, through the estimation of the resilience index of these cultures from the partial indicators of family farmers participation in the formation of aggregate GDP of the states of the Northeast, annual per capita amount of food yield in kilograms, per hectare and harvested area in hectares with rice, beans, cassava and maize. The variables were transformed into partial indices prior to aggregate for building resilience index. To measure the weights associated with each partial index it was used factorial analysis using the decomposition method of principal components. Once built the index of resilience of food family farming producer in the Northeast states, it was tested the impact of PRONAF on the index of resilience of each state. The data used in the research came from secondary sources collected in the Statistical Yearbooks IBGE - Institute of Geography and Statistics and the Central Bank of Brazil. The results showed that the participation of family farming aggregate in the Northeast, had a negative trend and Geometric Growth Rate (TGC) decreasing yearly. It was found different paths to the resilience indices estimated in the study. As the estimated these results probably reflect the climatic difficulties and the non - existent or deficient technical assistance services that prevail in all states of the region. It can be inferred that these factors probably led the behavior of the trend observed in the indices showed negative growth trend . Complementing, it was observed that, contrary to what would be expected, PRONAF, rural credit for the production of rice, bean, cassava and maize, have not been able to influence, from a statistical point of view, the indices of resilience in all states of Northeast period analyzed.